Peran Ekosistem Inovasi Lokal dalam Pembangunan UMKM - Yohan Purnawan; Melisa Nur Asima Sidabutar; William Gerry Sidabutar (Jurnal Pariwisata Tawangmangu, 2025)
This study examines the crucial role of local innovation ecosystems in supporting the development of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, particularly amid increasingly competitive global economic conditions that heighten the need for innovation. Evidence shows that innovation in products, marketing, and processes significantly contributes to MSME performance. The local innovation ecosystem involves key actors—universities, corporate venture capital, and incubators. Universities not only supply skilled human resources but also act as sources of knowledge and technology through research activities and collaboration with industry. Corporate ventures provide investment, professional mentoring, and market networks, while incubators offer ongoing support by providing facilities, training/mentoring, and access to professional networks to accelerate MSME growth. The synergy between innovation and ecosystem support is considered essential for creating added value, expanding market access, and optimizing MSME performance, including through digital transformation. The study uses a systematic literature review approach by analyzing 12 relevant articles published between 2015 and 2025 to provide a comprehensive picture of how local innovation ecosystems influence MSMEs